Analysis of the Need for Development of Fractions and Decimals Assessment Instruments Based on Wordwall for Upper Primary School Students - Agustina, Rina -; Sutopo, Yeri; Yuwono, Agus (Peneliti.net, 2025)
Upper-grade primary school students are required to master fractions and decimals as foundational knowledge for higher-level mathematics. Despite their importance, traditional assessment instruments often fail to capture students’ conceptual understanding and real-world application skills in this topic. This study aims to explore the necessity of developing an interactive assessment instrument based on Wordwall to evaluate students' comprehension of fractions and decimals in alignment with the Merdeka Curriculum and the cognitive characteristics of Phase C learners. A descriptive qualitative approach was employed, involving eight grade 5 and 6 teachers from Ciputih Village, Salem District, Brebes Regency, selected through purposive sampling. Data were gathered using questionnaires, semi-structured interviews, and curriculum document analysis, then analyzed using Miles, Huberman, and Saldaña's interactive model. The results revealed a strong need for assessment tools that are not only engaging and student-centered but also capable of measuring higher-order mathematical thinking. Teachers emphasized the relevance of digital game-based platforms like Wordwall in improving student motivation, facilitating contextual learning, and supporting meaningful assessment practices. These findings underscore the importance of developing reliable and enjoyable digital assessment instruments for fractions and decimals, supported by clear implementation guidelines and technopedagogical training for educators.